Solid catalyst component, catalyst, process for the preparation and process for the polymerization of olefins
Patent Information
- Application Number
- CN202510554957.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
中国专利CN 119219807A采用氯硅烷修饰的催化剂可以解决现有技术中粒径难以控制和易破碎的问题
Smart Images

Figure CN123003768A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst components for olefin polymerization, and more specifically, to a solid catalyst component for olefin homopolymerization and copolymerization, a method for preparing the same, a catalyst, and a method for olefin polymerization. Background Technology
[0002] Polyethylene, as the world's largest-produced synthetic resin, is the most widely used synthetic resin. Catalyst technology is a key core technology in the synthesis of polyethylene resin and a crucial breakthrough point for achieving high performance in polyethylene resin. With the continuous development of polyolefin catalyst technology, downstream enterprises are increasingly demanding higher performance from catalysts. In addition to catalyst activity and hydrogen regulation, long-term full-load operation of the plant is a core indicator of concern for enterprises. This requires that the polymerized powder have good particle morphology and flowability, and that the polymer has a high bulk density.
[0003] Alkoxymagnesium supported catalysts have become important catalysts for olefin polymerization due to their advantages such as good particle shape and excellent hydrogen regulation performance. However, the easily breakable nature of alkoxymagnesium catalysts during polymerization has made the bulk density and fine powder content of the polymer a focus of research, as these parameters affect the plant's load and operating cycle.
[0004] Chinese patent CN108341899A discloses a catalyst for ethylene polymerization or copolymerization, which uses long-chain alkanes, diesters, polyol esters, or 1,3-diether compounds as modifiers, resulting in a catalyst with high packing density and low fine powder content. Chinese patent CN119219807A uses a chlorosilane-modified catalyst to solve the problems of difficult particle size control and easy breakage in existing technologies. Chinese patent CN116041573A uses a pre-polymerization process to adjust catalyst performance. However, the optimization and improvement of existing technologies for alkoxymagnesium catalysts are still limited to the balance between performance characteristics, especially the balance between hydrogen regulation performance and polymer packing density and fine powder content.
[0005] Therefore, developing alkoxymagnesium catalysts for ethylene polymerization with excellent hydrogen regulation performance, high bulk density, and low fine powder content not only helps meet the requirements of high-load, long-cycle operation of the equipment, but also enables the equipment to achieve activity when producing bimodal materials or high melt index resin products, thus helping enterprises reduce costs and increase efficiency. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention proposes a solid catalyst component, a catalyst, its preparation method, and an olefin polymerization method for olefin polymerization. During the research process, this invention discovered that by introducing the compound represented by formula (Ⅰ) as an electron donor into the alkoxymagnesium catalyst system, the catalyst exhibits excellent hydrogen regulation performance and a significant increase in polymer bulk density when used for ethylene slurry polymerization / copolymerization.
[0007] A first aspect of the present invention provides a solid catalyst composition comprising reaction products of the following components:
[0008] 1) Magnesium complex;
[0009] The magnesium complex is selected from those with the general formula Mg(OR5). m (OR6) n (OR7) 2-m-n alkoxymagnesium compounds, wherein R5 and R6 are each independently selected from substituted or unsubstituted C1-C6 groups. 10 The hydrocarbon group, 0≤m≤2, 0≤n≤2; preferably, the magnesium complex includes, but is not limited to, Mg(OEt)2, Mg(OC3H7)2, Mg(OC4H9)2, and Mg(OEt). m (OEHA) 2-m Mg(OEt) m (OMe) n (OEHA) 2-m-n Mg(OEt) m (OiPr) n (OEHA) 2-m-n Mg(OC8H) 17 2. Mg(OEt) m (OMe) n (OBu) 2-m-n Mg(OEt) m (OBu) 2-m Mg(OEt) m (OiPr) n (OMe) 2-m-n Mg(OEt) m (OBu) n (OiPr) 2-m-n Mg(OEt) m (OiPr) 2-m Mg(OEt) m (OMe) 2-m At least one of them.
[0010] 2) Titanium-containing compounds;
[0011] The general formula of the titanium-containing compound is Ti(OR8).y X 4-y In the formula, R8 represents C1 to C2. 10 The hydrocarbon group, where X is a halogen atom, 0≤y≤3; preferably, R8 is selected from C1~C6 alkyl, C2~C6 alkenyl, C3 ... 10 cycloalkyl groups, or C6-C6 groups 10 The aromatic hydrocarbon group, more preferably, R8 is selected from methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, cyclopropyl, methylcyclopropyl, n-pentyl, methylcyclopentyl, cyclohexyl, phenyl, benzyl, or xylylyl; even more preferably, the titanium-containing compound includes, but is not limited to, at least one of TiCl4, Ti(OC2H5)Cl3, Ti(OCH3)Cl3, and Ti(OC4H9)Cl3. The titanium-containing compound can be added all at once during the reaction or added in stages.
[0012] The amount of the titanium-containing compound used per mole of magnesium is 1 to 50 mol, preferably 1 to 20 mol, for example, 1 mol, 5 mol, 10 mol, 20 mol, 30 mol, 40 mol, 50 mol, etc.
[0013] 3) An internal electron donor compound, wherein the internal electron donor compound is selected from at least one of the compounds shown in formula (I);
[0014]
[0015] In equation (Ⅰ), R1 and R2 are each independently selected from C1 to C2. 10 The hydrocarbon group, wherein the hydrogen atom in the above groups may be optionally replaced by hydroxyl, carboxyl, mercapto, guanidinyl, amide, amino, sulfonic acid, aldehyde, alkenyl, alkynyl, halogen atom, or phenyl.
[0016] Preferably, R1 and R2 are each independently selected from C1 to C8 hydrocarbon groups, wherein the hydrogen atoms in these groups may optionally be replaced by hydroxyl or alkenyl groups. More preferably, R1 and R2 are each independently selected from C1 to C8 alkyl groups, wherein the hydrogen atoms in these groups may optionally be replaced by hydroxyl or alkenyl groups.
[0017] More preferably, the compounds represented by formula (I) include, but are not limited to, methyl formate, ethyl formate, propyl formate, butyl formate, pentyl formate, hexyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, pentyl acetate, hexyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, hexyl butyrate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, pentyl butyrate, and hexyl butyrate. Ester, Methyl valerate, Ethyl valerate, Propyl valerate, Butyl valerate, Amyl valerate, Hexyl valerate, Methyl hexanoate, Ethyl hexanoate, Propyl hexanoate, Butyl hexanoate, Amyl hexanoate, Hexyl hexanoate, Ethyl 3-hydroxypropionate, Ethyl 3-hydroxybutyrate, Ethyl glycolate, Ethyl 2-hydroxypropionate, Ethyl serine, Methyl 3-hydroxypropionate, Methyl 3-hydroxybutyrate, Methyl glycolate, Methyl 2-hydroxypropionate, Methyl serine, 3- At least one of the following: propyl hydroxypropionate, propyl 3-hydroxybutyrate, propyl glycolate, propyl 2-hydroxypropionate, isopropyl 3-hydroxypropionate, isopropyl 2-hydroxypropionate, isopropyl glycolate, ethylene glycol monoester of 3-hydroxypropionate, ethyl 3-hydroxy-2-(hydroxymethyl)propionate, ethyl 2,3-dihydroxypropionate, tert-butyl 3-hydroxypropionate, butyl 3-hydroxybutyrate, butyl glycolate, butyl 2-hydroxypropionate, hexyl 3-hydroxypropionate, hexyl glycolate, hexyl 2-hydroxypropionate, methyl 2-hydroxybutyrate, ethyl 2-hydroxybutyrate, monoethyl glycerate, 2-(propionyloxy)ethanol, ethylene glycol monoacetate, hydroxyethyl acrylate, 2-hydroxyethylbutyrate, 2-hydroxyethylpropionate, and 2-hydroxypropyl acetate; the above internal electron donor compounds may be added all at once during the reaction or added in portions.
[0018] The amount of the internal electron-donating compound per mole of magnesium is 0.001 to 2 mol, preferably 0.001 to 1 mol, for example, 0.001 mol, 0.005 mol, 0.01 mol, 0.05 mol, 0.1 mol, 0.2 mol, 0.3 mol, 0.4 mol, 0.5 mol, 0.6 mol, 0.7 mol, 0.8 mol, 0.9 mol, 1.0 mol, 1.2 mol, 1.4 mol, 1.6 mol, 1.8 mol, 2 mol, etc.
[0019] According to embodiments of the present invention, the internal electron donor compound represented by formula (Ⅰ) can not only effectively adjust the type and number of active centers in the catalyst and control the catalyst's anti-breakage performance, but also regulate the pore structure of the catalyst during the transformation from support to catalyst, thereby increasing the polymer's packing density, while retaining the catalyst's high hydrogen regulation performance characteristics.
[0020] According to embodiments of the present invention, the solid catalyst component for olefin polymerization may further include aluminum compounds, including but not limited to at least one of Al(CH3)3, Al(CH2CH3)3, Al(i-Bu)3, AlH(CH2CH3)2, AlH(i-Bu)2, AlCl(CH2CH3)2, Al2Cl3(CH2CH3)3, and AlCl2(CH2CH3).
[0021] The amount of the aluminum compound used per mole of magnesium is 0.001 to 10 mol, preferably 0.01 to 5 mol, for example, it can be 0.001 mol, 0.005 mol, 0.01 mol, 0.05 mol, 0.1 mol, 0.5 mol, 1.0 mol, 1.5 mol, 2 mol, 2.5 mol, 3.0 mol, 3.5 mol, 4 mol, 4.5 mol, 5.0 mol, 6.0 mol, 7.0 mol, 8.0 mol, 9.0 mol, 10 mol, etc.
[0022] A second aspect of the present invention provides a method for preparing the solid catalyst component, the method comprising the following steps:
[0023] 1) The magnesium-containing complex is dispersed in an inert solvent to form a suspension;
[0024] 2) After cooling the suspension, it is contacted with a titanium-containing compound and an internal electron donor compound to obtain a solid slurry;
[0025] 3) Separate the solids in the solid slurry, wash the supernatant with an inert solvent, separate and dry to obtain the solid catalyst component; optionally, contact the supernatant with an aluminum compound or contact the aluminum compound with a solution of the obtained solid catalyst component.
[0026] In step 3), the solid catalyst precursor can be dried and re-prepared into a solution before contacting the organoaluminum compound, or it can be washed with an inert solvent and then directly reacted with the inert solvent and aluminum compound.
[0027] The amount of the internal electron-donating compound per mole of magnesium is 0.001–2 mol, preferably 0.001–1 mol; the amount of the titanium-containing compound is 1–50 mol, preferably 1–20 mol. When an aluminum compound is included, the amount of the aluminum compound is 0.001–10 mol, preferably 0.01–5 mol.
[0028] Each of the inert solvents is independently selected from at least one of aromatic compounds or alkane compounds; preferably, each of the inert solvents is independently selected from at least one of benzene, toluene, hexane, heptane, octane, decane, xylene, white oil, paraffin, or silicone oil.
[0029] In step 2) or 3), the contact temperature is -20℃ to 110℃.
[0030] A third aspect of the present invention provides a catalyst system for olefin polymerization, the catalyst system comprising the following components:
[0031] Component I: The solid catalyst component described above or the solid catalyst component obtained by the preparation method described above;
[0032] Component II: General formula AlR d X 3-d Organoaluminum compounds, wherein the repeated Rs are independently hydrogen or C. l ~C 20 Hydrocarbon group, X is a halogen atom, 0 <d≤3。
[0033] In the organoaluminum compound, the repeated R is independently hydrogen or C1-C2. 10 The hydrocarbon group; preferably, the repeated R is independently hydrogen or a C1-C5 hydrocarbon group; more preferably, the organoaluminum compound is selected from at least one of Al(CH3)3, Al(CH2CH3)3, Al(i-Bu)3, AlH(CH2CH3)2, AlH(i-Bu)2, AlCl(CH2CH3)2, Al2Cl3(CH2CH3)3, and AlCl2(CH2CH3).
[0034] The molar ratio of aluminum in component II to titanium in component I is 10:1 to 200:1, preferably 20:1 to 200:1, and can be, for example, 10:1, 20:1, 50:1, 80:1, 100:1, 120:1, 150:1, 180:1, 200:1, etc.
[0035] A fourth aspect of the present invention provides a method for olefin polymerization, the method comprising contacting one or more olefins with the catalyst described above under olefin polymerization reaction conditions.
[0036] The polymerization method can be used for olefin homopolymerization or α-olefin copolymerization.
[0037] The olefin is preferably at least one selected from ethylene, propylene, butene, and hexene.
[0038] This invention provides a solid catalyst component, preparation method, catalyst system, and olefin polymerization method for ethylene polymerization or copolymerization. When used for homopolymerization of ethylene or copolymerization with α-olefins, this solid catalyst component exhibits excellent hydrogen regulation performance, resulting in polymers with high bulk density and low fine powder content. Detailed Implementation
[0039] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0040] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0041] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0042] In the following examples and comparative examples:
[0043] 1. The relative weight percentage of titanium in the solid catalyst components was characterized by spectrophotometry.
[0044] 2. Bulk density of polymer: determined by the method of weight of loose solids per unit volume (GB / T1636).
[0045] 3. The content of polymer fine powder is determined by sieving 100g of powder through a 200-mesh (75μm) sieve. The amount of polymer passing through the sieve is recorded as W, and the content of fine powder is W.
[0046] 4. Determination of polymer melt index (MI): According to ASTM D1238-99, the MI was determined at a load of 2.16 kg and a temperature of 190 °C.
[0047] 5. All pressures mentioned in the polymerization reaction are absolute pressures:
[0048] ① Polymerization reaction with low hydrogen / ethylene ratio
[0049] A 2L stainless steel reactor was fully purged with high-purity nitrogen, then 1L of hexane and 2.0mL of 1M triethylaluminum solution were added, followed by the solid catalyst components (containing 0.6mg titanium) prepared in the examples and comparative examples. The temperature was raised to 70°C, and hydrogen was introduced to bring the pressure inside the reactor to 0.28MPa. Ethylene was then introduced to bring the total pressure inside the reactor to 0.73MPa, and polymerization was carried out at 80°C for 2 hours.
[0050] ② Polymerization reaction with high hydrogen / ethylene ratio
[0051] A 2L stainless steel reactor was fully purged with high-purity nitrogen, then 1L of hexane and 2.0mL of 1M triethylaluminum were added, followed by the solid catalyst components (containing 2mg titanium) prepared in the examples and comparative examples. The temperature was raised to 70°C, and hydrogen was introduced to bring the pressure inside the reactor to 0.58MPa. Ethylene was then introduced to bring the total pressure inside the reactor to 0.73MPa, and polymerization was carried out at 85°C for 2 hours.
[0052] The present invention will be further described below with reference to specific embodiments.
[0053] Example 1
[0054] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise, followed by 1 mL of methyl propionate. After the reaction was completed, the temperature was raised to 80 °C and held at that temperature for 2 h. The mixture was allowed to settle, and the supernatant was decanted, washed four times with hexane, separated, and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0055] Example 2
[0056] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise, followed by 1 mL of ethyl acetate. After the reaction was complete, the temperature was raised to 80 °C and held at that temperature for 2 h, then held at that temperature for another 1 h. The mixture was allowed to settle, and the supernatant was decanted, washed four times with hexane, separated, and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0057] Example 3
[0058] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise with stirring. Then, 1 mL of ethyl glycolate was added. After the reaction was completed, the temperature was raised to 80 °C and held at that temperature for 2 h. The mixture was allowed to settle, and the supernatant was decanted, washed four times with hexane, separated, and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0059] Example 4
[0060] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise, followed by 1 mL of ethyl acetate. After this, the temperature was raised to 80 °C and held at that temperature for 2 h, then held at that temperature for another 1 h. The mixture was allowed to settle, and the supernatant was decanted and washed three times with hexane. 0.5 mL of 1 M triethylaluminum solution was added at 50 °C, and the mixture was stirred for 2 h. The mixture was allowed to settle, and the supernatant was decanted and washed four times with hexane. After separation and drying, a solid catalyst with good flowability was obtained. The catalyst composition and polymerization results are shown in Table 1.
[0061] Example 5
[0062] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise, followed by 1 mL of ethyl acetate. After this, the temperature was raised to 80 °C and held at that temperature for 2 h, then held at that temperature for another 1 h. The mixture was allowed to settle, and the supernatant was decanted and washed three times with hexane. 3 mL of 1 M triethylaluminum solution was added at 50 °C, and the mixture was stirred for 2 h. The mixture was allowed to settle, and the supernatant was decanted and washed four times with hexane. The mixture was then separated and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0063] Example 6
[0064] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise, followed by 1 mL of ethyl acetate. After this, the temperature was raised to 80 °C and held at that temperature for 2 h, then held at that temperature for another 1 h. The mixture was allowed to settle, and the supernatant was decanted and washed three times with hexane. 1.5 mL of 1 M triethylaluminum solution was added at room temperature, and the mixture was stirred for 48 h. The mixture was allowed to settle, and the supernatant was decanted and washed four times with hexane. The mixture was then separated and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0065] Example 7
[0066] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise with stirring. Then, 1.2 mL of ethyl 2-hydroxypropionate was added. After the reaction was completed, the temperature was raised to 80 °C and held at that temperature for 2 h. The mixture was allowed to settle, and the supernatant was decanted, washed four times with hexane, separated, and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0067] Example 8
[0068] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise with stirring. Then, 1.2 mL of ethyl 2-hydroxypropionate was added. After the reaction was complete, the temperature was raised to 80 °C and held at that temperature for 2 h. The mixture was allowed to settle, and the supernatant was decanted and washed three times with hexane. 1.5 mL of 1 M triethylaluminum solution was added at room temperature, and the mixture was stirred for 48 h. The mixture was allowed to settle, and the supernatant was decanted and washed four times with hexane. After separation and drying, a solid catalyst with good flowability was obtained. The catalyst composition and polymerization results are shown in Table 1.
[0069] Comparative Example 1
[0070] In a 300 mL stirred 5-necked reactor fully purged with nitrogen, 4 g of magnesium ethoxylate support with an average particle size of 12 μm and 40 mL of toluene were added. The mixture was cooled to -15 °C, and 20 mL of TiCl4 was slowly added dropwise with stirring. After the addition was complete, the temperature was raised to 80 °C and held at that temperature for 2 h. The mixture was allowed to settle, and the supernatant was decanted, washed four times with hexane, separated, and dried to obtain a solid catalyst with good flowability. The catalyst composition and polymerization results are shown in Table 1.
[0071] Comparative Example 2
[0072] 4.0 g magnesium chloride, 50 mL toluene, 3.0 mL epichlorohydrin, 9 mL tri-n-butyl phosphate, and 4.4 mL ethanol were added to a reactor. The reaction was carried out at 70 °C for 2 hours until the magnesium chloride was completely dissolved. The system was then cooled to -10 °C, and 70 mL titanium tetrachloride was slowly added dropwise, followed by 3 mL tetraethoxysilane. The temperature was slowly raised to 85 °C and maintained at this temperature for 2 hours. After standing, the mixture was decanted, and the solid catalyst was washed several times with hexane. After drying, a solid catalyst component with good flowability was obtained. The catalyst composition and polymerization results are shown in Table 1.
[0073] The performance parameters of the catalysts and polymers used in the examples and comparative examples are shown in Table 1.
[0074] Table 1
[0075]
[0076] As shown in Table 1, when the catalyst of the present invention is used for ethylene polymerization, compared with Comparative Example 1, the introduction of the electron donor compound shown in Formula (I) and an optional aluminum compound into the catalyst results in increased bulk density of the polymerized powder, decreased fine powder content, and minimal decrease in activity. Compared with Comparative Example 2, the catalyst provided by the present invention exhibits significantly improved high hydrogen melt index and polymer bulk density. These results indicate that the catalyst of the present invention has superior overall performance compared to the comparative catalyst.
[0077] The embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A solid catalyst component comprising a reaction product of the following components: 1) Magnesium complex; 2) Titanium-containing compounds; 3) An internal electron donor compound, wherein the internal electron donor compound is selected from at least one of the compounds shown in formula (I); R1 and R2 are each independently selected from C1 to C2. 10 The hydrocarbon group, wherein the hydrogen atom in the above groups may be optionally replaced by hydroxyl, carboxyl, mercapto, guanidine, amide, amino, sulfonic acid, aldehyde, alkenyl, alkynyl, halogen atom, or phenyl.
2. The solid catalyst component according to claim 1, characterized in that: R1 and R2 are each independently selected from C1-C8 hydrocarbon groups, preferably C1-C8 alkyl groups, wherein the hydrogen atoms in the above groups may optionally be replaced by hydroxyl or alkenyl groups; preferably, the compound represented by formula (I) is selected from methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, hexyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, amyl acetate, hexyl acetate, methyl propionate, ethyl propionate, propionyl propionate Ester, Butyl propionate, Amyl propionate, Hexyl propionate, Methyl butyrate, Ethyl butyrate, Propyl butyrate, Butyl butyrate, Amyl butyrate, Hexyl butyrate, Methyl valerate, Ethyl valerate, Propyl valerate, Butyl valerate, Amyl valerate, Hexyl valerate, Methyl hexanoate, Ethyl hexanoate, Propyl hexanoate, Butyl hexanoate, Amyl hexanoate, Hexyl hexanoate, Ethyl 3-hydroxypropionate, Ethyl 3-hydroxybutyrate, Ethyl glycolate, Ethyl 2-hydroxypropionate, Ethyl serine, 3 Methyl 3-hydroxypropionate, methyl 3-hydroxybutyrate, methyl glycolate, methyl 2-hydroxypropionate, serine methyl ester, propyl 3-hydroxypropionate, propyl 3-hydroxybutyrate, propyl glycolate, propyl 2-hydroxypropionate, isopropyl 3-hydroxypropionate, isopropyl 2-hydroxypropionate, isopropyl glycolate, ethylene glycol monoester of 3-hydroxypropionate, ethyl 3-hydroxy-2-(hydroxymethyl)propionate, ethyl 2,3-dihydroxypropionate, tert-butyl 3-hydroxypropionate At least one of the following: ester, butyl 3-hydroxybutyrate, butyl glycolate, butyl 2-hydroxypropionate, hexyl 3-hydroxypropionate, hexyl 3-hydroxybutyrate, hexyl glycolate, hexyl 2-hydroxypropionate, methyl 2-hydroxybutyrate, ethyl 2-hydroxybutyrate, monoethyl glycerate, 2-(propionyloxy)ethanol, ethylene glycol monoacetate, hydroxyethyl acrylate, 2-hydroxyethylbutyrate, 2-hydroxyethylpropionate, and 2-hydroxypropyl acetate; and / or, The magnesium complex is selected from those with the general formula Mg(OR5)m(OR6)n(OR7). 2-m-n alkoxymagnesium compounds, wherein R5 and R6 are each independently selected from substituted or unsubstituted C1-C6 groups. 10 The hydrocarbon group, 0≤m≤2, 0≤n≤2; preferably, the magnesium complex is selected from Mg(OEt)2, Mg(OC3H7)2, Mg(OC4H9)2, Mg(OEt) m (OEHA) 2-m Mg(OEt) m (OMe) n (OEHA) 2-m-n Mg(OEt) m (OiPr) n (OEHA) 2-m-n Mg(OC8H) 17 2. Mg(OEt) m (OMe) n (OBu) 2-m-n Mg(OEt) m (OBu) 2-m Mg(OEt) m (OiPr) n (OMe) 2-m-n Mg(OEt) m (OBu) n (OiPr) 2-m-n Mg(OEt) m (OiPr) 2-m Mg(OEt) m (OMe) 2-m At least one of them; and / or, The general formula of the titanium-containing compound is Ti(OR8). y X 4-y In the formula, R8 represents C1 to C2. 10 The hydrocarbon group, where X is a halogen atom, 0≤y≤3; preferably, R8 is selected from C1~C6 alkyl, C2~C6 alkenyl, C3 ... 10 cycloalkyl groups, or C6-C6 groups 10 The aromatic hydrocarbon group; more preferably, R8 is selected from methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, cyclopropyl, methylcyclopropyl, n-pentyl, methylcyclopentyl, cyclohexyl, phenyl, benzyl, or xylylyl; even more preferably, the titanium-containing compound is selected from at least one of TiCl4, Ti(OC2H5)Cl3, Ti(OCH3)Cl3, and Ti(OC4H9)Cl3.
3. The solid catalyst component according to claim 1, characterized in that: The amount of the internal electron donor compound per mole of magnesium is 0.001–2 mol, preferably 0.001–1 mol; the amount of the titanium-containing compound is 1–50 mol, preferably 1–20 mol.
4. The solid catalyst component according to any one of claims 1 to 3, characterized in that: The solid catalyst component also includes aluminum compounds.
5. The solid catalyst component according to claim 4, characterized in that: The aluminum compound is selected from at least one of Al(CH3)3, Al(CH2CH3)3, Al(i-Bu)3, AlH(CH2CH3)2, AlH(i-Bu)2, AlCl(CH2CH3)2, AlCl2(CH2CH3), and Al2Cl3(CH2CH3)3; and / or, The amount of the aluminum compound used per mole of magnesium is 0.001 to 10 mol, preferably 0.01 to 5 mol.
6. A method for preparing the solid catalyst component according to any one of claims 1 to 5, comprising the following steps: 1) The magnesium-containing complex is dispersed in an inert solvent to form a suspension; 2) After cooling the suspension, it is contacted with a titanium-containing compound and an internal electron donor compound to obtain a solid slurry; 3) Separate the solids in the solid slurry, wash the supernatant with an inert solvent, separate and dry to obtain the solid catalyst component; optionally, contact the supernatant with an aluminum compound or contact the aluminum compound with a solution of the obtained solid catalyst component.
7. The method for preparing the solid catalyst component according to claim 6, characterized in that: In step 1) or step 3), each of the inert solvents is independently selected from at least one of aromatic compounds or alkane compounds; preferably, each of the inert solvents is independently selected from at least one of benzene, toluene, hexane, heptane, octane, decane, xylene, white oil, paraffin, or silicone oil.
8. A catalyst for olefin polymerization, comprising the following components: Component I: The solid catalyst component according to any one of claims 1 to 5 or the solid catalyst component obtained by the preparation method according to any one of claims 6 to 7; Component II: General formula AlR d X 3-d Organoaluminum compounds, wherein the repeated R is independently hydrogen or C1-C2. 20 The hydrocarbon group, where X is a halogen atom, 0 <d≤3。 9. The catalyst according to claim 8, characterized in that: The molar ratio of aluminum in component II to titanium in component I is 10:1 to 200:1, preferably 20:1 to 200:1; and / or, In the organoaluminum compound, the repeated R is independently hydrogen or C1-C2. 10 The hydrocarbon group; preferably, the repeated R is independently hydrogen or a C1-C5 hydrocarbon group; more preferably, the organoaluminum compound is selected from at least one of Al(CH3)3, Al(CH2CH3)3, Al(i-Bu)3, AlH(CH2CH3)2, AlH(i-Bu)2, AlCl(CH2CH3)2, Al2Cl3(CH2CH3)3, and AlCl2(CH2CH3).
10. A method for olefin polymerization, comprising: Under olefin polymerization reaction conditions, one or more olefins are contacted with the catalyst described in any one of claims 8 to 9.
Citation Information
Patent Citations
Alkoxymagnesium carrier-based catalyst component for ethylene polymerization or copolymerization and preparation method and use thereof
CN108341899A
Polyolefin catalyst prepolymerization method, polyolefin polymerization method and application thereof
CN116041573A
Method for preparing catalyst and catalyst prepared by method
CN119219807A
